Development of Wing Media (Wordwall Interactive Games) for Cube and Rectangular Prism Concept - Musawamah, Siti; Zaafarani, Nadiah; Qurrotul Aini, Nihlah; Firdaus, Firdaus (Jurnal keilmuan dan Kependidikan dasar, 2026)
Mathematics learning is often perceived as difficult and less engaging by students due to teacher-centered instruction, less varied teaching strategies, and limited learning media. These conditions cause classroom activities to become passive and hinder students' understanding of the material. This study aims to develop and analyze the feasibility and practicality of WING (Wordwall Interactive Games) media on the topic of three-dimensional shapes. The research method used was Research and Development (R&D) with the ADDIE model. The research subjects involved 28 fifth-grade students of SD Negeri Tembong 1, consisting of 12 students in the small-group trial and all students in the large-group trial. Data collection techniques included observation, interviews, expert validation, and student response questionnaires. The results showed that the WING media achieved a “highly feasible” criterion, with a media expert validation score of 95.4% and a material expert validation score of 96.4%. In addition, the practicality test results based on student response questionnaires obtained a score of 87%, categorized as “highly practical.” Therefore, the WING media is valid and practical to be used as a mathematics learning medium for the topic of cube and rectangular principles.